Design of T-Shaped Micropump Based on Induced Charge Electroosmotic - Kai Zhang; Xiaojing Mi; Bingying Sheng (Abstract and Applied Analysis)
The fluid-driven efficiency of the micropump based on induced charge electroosmotic was studied by numerical simulation method. In this paper, we propose to make some improvement against the T-shaped piping design of micropump, and we embed a janus cylinder in the junction of the T-shaped pipe for the micropump design. We offer different voltage to the inlet of the pipe and carry out the numerical study of the fluid field induced by the cylinder, and the comparison of the velocity and flux of the outlet in different voltage as carried out. It is found that there are two symmetrical circulations around the polarizable side of the cylinder. And the comparison results show that the flow and the velocity of the outlet were increased with the increasing voltage of the entrance.